Transcriptome analysis unveils survival strategies of Streptococcus parauberis against fish serum. - Yoonhang Lee; Nameun Kim; HyeongJin Roh; Ahran Kim; Hyun-Ja Han; Miyoung Cho; Do-Hyung Kim (PLoS ONE)
Streptococcus parauberis is an important bacterial fish pathogen that causes streptococcosis in a variety of fish species including the olive flounder. Despite its importance in the aquaculture industry, little is known about the survival strategy of S. parauberis in the host. Therefore, the objective of this study was to produce genome-wide transcriptome data and identify key factors for the survival of S. parauberis SPOF3K in its host. To this end, S. parauberis SPOF3K was incubated in olive flounder serum and nutrient-enriched media as a control. Although S. parauberis SPOF3K proliferated in both culture conditions, the transcriptomic patterns of the two groups were very different. Interestingly, the expression levels of genes responsible for the replication of an S. parauberis plasmid in the presence of olive flounder serum were higher than those in the absence of olive flounder serum, indicating that this plasmid may play an important role in the survival and proliferation of S. parauberis in the host. Several ATP-binding cassette transporters known to transport organic substrates (e.g., biotin and osmoprotectants) that are vital for bacterial survival in the host were significantly up-regulated in S. parauberis cultured in serum. In addition, groEL, dnaK operon, and members of the clp protease family, which are known to play important roles in response to various stressors, were up-regulated in S. parauberis incubated in serum, thus limiting damage and facilitating cellular recovery. Moreover, important virulence factors including the hyaluronic acid capsule (has operon), sortase A (srtA), C5a peptidase (scp), and peptidoglycan O-acetyltransferase (oatA) were significantly upregulated in S. paraubers in serum. These results indicate that S. paraubers can resist and evade the humoral immune responses of fish. The transcriptomic data obtained in this study provide a better understanding of the mode of action of S. parauberis in fish.